2012
DOI: 10.1007/s10544-012-9718-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic nanoscreening of circulating tumor cells with a motion controlled microfluidic system

Abstract: Combining the power of immunomagnetic assay and microfluidic microchip operations, we successfully detected rare CTCs from clinical blood samples. The microfluidic system is operated in a flip-flop mode, where a computer-controlled rotational holder with an array of microfluidic chips inverts the microchannels. We have demonstrated both theoretically and experimentally that the direction of red blood cell (RBC) sedimentation with regards to the magnetic force required for cell separation is important for captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 29 publications
1
60
0
Order By: Relevance
“…They are very weakly magnetized 1mm thick elastic sheets (AFG-13346 Magnet Sheets, ProMAG Products, Marietta, OH ). In our previous study, we measured the magnetic field induced by the spacer to be small enough to be neglected and they can be treated as simple distance offset [28]. It is noteworthy that the spacers only cover the front part of the channel so that the strong magnetic field in the later part of the channel can prevent potential CTCs loss.…”
Section: Methodsmentioning
confidence: 99%
“…They are very weakly magnetized 1mm thick elastic sheets (AFG-13346 Magnet Sheets, ProMAG Products, Marietta, OH ). In our previous study, we measured the magnetic field induced by the spacer to be small enough to be neglected and they can be treated as simple distance offset [28]. It is noteworthy that the spacers only cover the front part of the channel so that the strong magnetic field in the later part of the channel can prevent potential CTCs loss.…”
Section: Methodsmentioning
confidence: 99%
“…When an antibody with high specificity is used, high recovery efficiencies are possible with excellent depletion of contaminating cells at high throughput. The work of Plouffe et al (Plouffe et al, 2012) and Huang et al (Huang et al, 2012) are two good examples in which the throughput was of the order of hundreds of millions to a billion cells per minute. Plouffe et al (Plouffe et al, 2012) reported recovery of spiked CTCs or primary haematopoietic stem cells (HSCs) from whole blood with efficiencies of 88% and 97%, whilst Huang et al (Huang et al, 2012) successfully detected CTCs from cancer patients with recovery efficiencies rounding 60% to 70%.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Depending on whether a nanoparticle seeks a vascular, a deep tissue or a blood-circulating target, the design of a nanoparticle requires different considerations and features. For example, ligand-functionalized magnetic iron oxide nanoparticles can bind to CTCs, which can be captured using immunomagnetic separation [33, 34]. In the case targeting metastasis, vascular targeting may be more effective than deep tissue targeting (which requires the EPR effect).…”
Section: Obstacles To the Widespread Use Of Nanoparticle Imaging Amentioning
confidence: 99%